THE INSTRUMENT TO MEASURE ENGLISH PROFICIENCY OF THE PROSPECTIVE EMPLOYEES: BETWEEN TOEFL AND TOEIC - Besin Gaspar; Yenny Hartanto (Jurnal Bisnis Terapan, 2018)
Recently the university students are required by their institutions to have the TOEFL score in the fisrt year or in the last year of their study before graduation. Some other higher institutions require their students to submit TOEIC, not TOEFL, before graduation. Companies, in the recruitment process, require the applicants to submit TOEFL score to show their level of English proficiency. The first question is which one is more appropriate for job applicants in the compay: TOEFL or TOEIC. Another question for university students before graduation is whether to have TOEFL in the first year or in the last year before graduation. This article aims at answering the two questions raised. The first part will give an overview of various versions of TOEFL and TOEIC and the second part proposes the appropriate English proficiency test for the recruitment process for new employees and for the university graduates, that is, TOEIC for the company and TOEFL for universities and colleges.